Children and the self-knowledge acquired from children's stories - Gimene Cardozo Braga; Luciane Prado Kantorski; Valéria Cristina Christello Coimbra; Janaína Quinzen Willrich (Universidade Federal de Santa Maria, 2015)
Aim: to verify the self-knowledge children acquire by storytelling on specific children health themes. Method: it is a descriptive-exploratory qualitative study that utilized as instruments children's stories with themes about disorders: childhood depression, attention deficit and hyperactivity disorder. Two meetings were held in a child mental health service, with children between 6 and 10 years old. It was used the method of storytelling and the technique of the operative group. Results: the stories appeared as mediators able to assist nursing by listening to the children's lives and affection. Children's self-knowledge was shown by identification of their own feelings with the characters' feelings besides the difficulties in relationships and learning. Final remarks: those stories enabled teaching on health, as well as to promote mental health through the child identification-projection manifestation